Strengthening teachers' performance in deep learning-integrated project-based learning - Nurwidodo, N.; Hindun, Iin; Wahyuni, Sri (Journal of Community Service and Empowerment, 2026)
Deep learning-oriented instruction, characterized by meaningful, mindful, and joyful learning, is increasingly promoted as a pathway to strengthen 21st-century learning. However, many teachers still experience conceptual and procedural difficulties when implementing project-based learning in ways that genuinely engage students in inquiry, collaboration, and problem solving. This community service program aimed to strengthen teachers' performance in Deep Learning-integrated Project-Based Learning (DL-PjBL) among Muhammadiyah junior secondary school teachers in Batu City, Indonesia. The program was implemented from June to December 2025 and involved 20 teachers from multiple subject areas. Program stages included socialization, intensive workshop sessions, guided module development, classroom implementation, mentoring, and reflection. Quantitative data were obtained from expert reviews of teaching modules and classroom observations of four model teachers, using a five-point performance rubric across six DL-PjBL stages: driving question, project planning, scheduling, monitoring, assessment, and reflection. Descriptive analysis showed clear improvement after the intervention. In module design, mean scores increased from 1.4-1.8 before the workshop to 3.0-3.5 after the workshop. In classroom practice, mean scores improved from 1.4-1.8 to 2.5-3.5. The greatest gains were observed in project planning, scheduling, and monitoring, while product assessment and reflection still required reinforcement during classroom implementation. Qualitative reflections indicated stronger teacher understanding of problem positioning, greater confidence in designing contextual projects, and more positive attitudes toward active and collaborative learning. Overall, the mentoring program strengthened teachers' understanding, skills, and professional appreciation of DL-PjBL and demonstrated their growing readiness to implement more meaningful, mindful, and joyful learning in school practice.